Rancang Bangun Sistem Informasi Employee Attendance pada PT.TNT Skypak Internasional - Desy Apriani; Po. Abas Sunarya; Tinton Yuan Permono (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2021)
PT.TNT Skypak Internasional is a foreign company doing business in Indonesia and is located in the Soekarno-Hatta airport area. PT.TNT Skypak Internasional focuses on export and import freight forwarding. Currently there are problems in the employee attendance process / Employee Attendance, because it is still being run manually, so the Employee Attendance data retrieval is time consuming and time inefficient. For this reason, a website-based Employee Attendance information system is needed as a solution to the problems that occur at PT.TNT Skypak Internasional. The research method used is Data Collecting Methods such as Observation, Interview and Library Research, then the design analysis method uses UML diagrams and database design with PHP and MySQL. The research results of this journal paper are Website-based Employee Attendance Information System Design to be applied to PT.TNT Skypak Internasional.